Mocking Laughter: The Political Humor of Indonesians Portrayed in Newspaper Cartoons - Nugraha, Danang Satria (Universitas Negeri Semarang, 2023)
This study delves into the crucial role of political humor in Indonesian society by conducting a thorough analysis of newspaper cartoons through critical discourse analysis. Humor is a potent tool for expressing social commentary and political critique in a less confrontational manner. The study focuses on meticulously chosen cartoons published in major Indonesian newspapers, i.e. Kompas, to uncover the underlying political themes, satirical techniques, and social implications conveyed through humor. The study examines how these cartoons shape public discourse, challenge power structures, and influence public opinion. By thoroughly analyzing linguistic and visual elements, the study offers valuable insights into how political humor functions as a form of resistance, social commentary, and cultural expression in Indonesia. The findings provide a deeper understanding of the complex interplay between humor, politics, and society, highlighting how Indonesians use satire to navigate and negotiate their socio-political landscape. This study significantly contributes to the critical discourse analysis field by emphasizing the multifaceted role of political humor in shaping public discourse and fostering critical engagement within a specific cultural and political context in Indonesia.